Family Dynamics and Falling in Love in People with Disabilities - Ponce, Freddy (2021)
The purpose of this paper is to analyze the dynamics of families that include a member with disabilities who is in the process of falling in love and having a relationship. This member will experience a negative impact from her/his family, due to certain beliefs and prejudices, that will hinder in her/his social and emotionaldevelopment on his/her development. In this article, we explore the love experience in individuals with disabilities to understand the dynamics between family and the member with disabilities. As a result of the challenges these people encounter at the individual and family level; I propose guidelines, based on the theoretic and systemic social and psychotherapeutic frame, for the intervention, as well as rules for the follow up in the process of engaging in love.